ANGKA KEBERHASILAN DAN KOMPLIKASI PCNL PADA PASIEN BATU GINJAL DI RUMAH SAKIT CIPTO MANGUNKUSUMO TAHUN 1999 – 2006 - Murti, Bimanggono Hernowo; Rasyid, Nur (Indonesian Urological Association, 2008)
Objective: To study the results of renal stones treatment with PCNL in terms of complication and stone free rate in Cipto Mangunkusumo Hospital. Material & methods: Retrospective study of renal stone patients who were treated with PCNL at the Department of Urology, Cipto Mangunkusumo Hospital from January 1st 1999 until May 31st 2006. Results: There were 213 patients between 8 until 80 years old done for various stone localizations in the kidney. The overall stone free rate was 74,2%. The complication rate was 10,8%, bleeding in 15 patients (7,1%), leakage in 5 patients (2,3%), and colon perforation in 3 patients (1,4%). There was no artery + vena renalis perforation, urosepsis, hydro/pneumothorax or mortality in this group. Results are similar with experience in the literature. Conclusion: PCNL is a safe procedure for renal stones removal. It gives satisfactory results as well as a low complication rate, but if complications occur the morbidity can be severe. Hence, this procedure has to be done very meticulously.